PENGARUH TANGGUNG JAWAB SOSIAL PERUSAHAAN TERHADAP MANAJEMEN LABA DENGAN KONSERVATISME AKUNTANSI SEBAGAI VARIABEL MEDIASI DAN TATA KELOLA PERUSAHAAN SEBAGAI VARIABEL MODERASI (Studi Empiris pada Perusahaan Indonesia yang Terdaftar di BEI Periode 2021–2024) - Hanif Naufal Mokoputra; Dwi Ratmono (Diponegoro Journal of Accounting, 2026)
This study aims to examine the effect of corporate social responsibility on earnings management, with accounting conservatism as a mediating variable and corporate governance as a moderating variable, in non-financial companies listed on the Indonesia Stock Exchange during the 2021–2024 period. Corporate social responsibility is measured using the Bloomberg Environmental Disclosure Score and Bloomberg Social Disclosure Score, earnings management is measured using the absolute value of discretionary accruals, accounting conservatism is measured using the Givoly and Hayn model, and corporate governance is measured using the Bloomberg Governance Score. The research sample was selected using purposive sampling, resulting in 505 observations. The data were analyzed using Partial Least Square-Structural Equation Modelling (PLS-SEM) with SmartPLS 3.The results show that corporate social responsibility has a negative and significant effect on earnings management. However, corporate social responsibility does not have a significant effect on accounting conservatism, and accounting conservatism does not have a significant effect on earnings management. Furthermore, corporate governance is proven to moderate the relationship between accounting conservatism and earnings management. Meanwhile, accounting conservatism is unable to mediate the effect of corporate social responsibility on earnings management. These findings indicate that corporate social responsibility disclosure directly contributes to reducing earnings management practices, but not through accounting conservatism as a mediating mechanism.